Enhancing Mentor Teacher Practices through Jelita-Lestari: Developing an Online Journal System for Reflective Collaboration in Teacher Education - Ibrohim, Ibrohim; Muksar, Makbul; Yulianti, Erni; Hajar, Maya Umi (Prosiding Seminar Nasional Pengabdian kepada Masyarakat (SINAPMAS), 2024)
The quality of mentoring mentor teachers provide during the teaching practicum of pre-service teacher education programs significantly impacts the pedagogical competence of prospective teachers. The current study addresses the challenge of enhancing the quality of mentoring provided by mentor teachers in the teaching practicum of the Teacher Professional Education program in the Science Education Study Program at the State University of Malang. The research focuses on developing and implementing "Jelita-Lestari," an online journal system based on lesson study, to optimize the quality of mentoring. The system aims to provide a platform for mentor teachers to document their mentoring processes, track student progress, and publish articles related to their experiences, fostering reflective practice and knowledge sharing. Implementing Jelita-Lestari is expected to improve pedagogical competence among prospective science teachers by facilitating systematic mentoring and promoting a collaborative learning community among mentor teachers. The study underscores the importance of continuous professional development for mentor teachers and the potential of technology-enhanced tools in supporting effective mentoring practices. Keywords—Jelita Lestari, Mentor Teacher Quality, Technology Integration, Professional Development, Lesson Study, Online Journal System.